0,3 ( 15 x - 3 ) = 5 - ( - 6 + x )

саня2271337 саня2271337    3   06.09.2021 18:51    0

Ответы
lika360 lika360  06.09.2021 19:00

Пошаговое объяснение:

0,3 ( 15 x - 3 ) = 5 - ( - 6 + x )

4,5x - 0,9 = 5 + 6 - x

4,5x - 0,9 = 11 - x

4,5x + x = 11 + 0,9

5,5x = 11,9

x = 11,9 : 5,5

x = 2 9/55

ПОКАЗАТЬ ОТВЕТЫ
vanyushkachushka79 vanyushkachushka79  06.09.2021 19:00

Пошаговое объяснение:

0,3 ( 15 x - 3 ) = 5 - ( - 6 + x )

4,5х-0,9=5+6-х

4,5х+х=11-0,9

4,5х=10,1

х=10,1:4,5

х=2 11/45

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика